The Relationship of baseline Hba1c with visual , anatomical outcome and frequency of bevacizumab at 1 year in diabetic macular edema in a trust based hospital , Karachi - zaka, royala; khan, Burhan Abdul Majid; sabri, Mirza Zakiuddin Ahmed; Qureshi, Rabia (Pakistan Journal of Ophthalmology, 2020)
Objective: To evaluate the relationship of baseline Hemoglobin A1c (HbA1c) with visual, anatomical outcomes and frequency of cost effective bevacizumab at 12 months in eyes of diabetic macular edema (DME) in a developing country . Study Design: Retrospective cross sectional comparative data. Place and Duration of Study: Prevention of blindness (POB), Karachi, Pakistan between October 2018 and sept 2019. Methodology: It is a comparative cross sectional retrospective study. A total of 280 patients with DME presenting to the eye OPD of POB who did not receive any treatment before in the absence of concurrent retinal disease and treated with at least 3 intravitreal injections of bevacizumab and who completed the follow-up of 12 months included in the study. Results: There were 280 patients , male were 149 (53.2%) and female 131 (46.8%), 95% patients age 50 years. Patients divided into 3 groups n= 20 (7.1%) , 187 (66.8%) and 73 (26.1%) patients with Hba1c <7.0 , 7.1-8.0 and > 8.0 respectively. Central macular thicknesss decreased significantly from baseline in all 3 groups with vision improved the most in group 1 <7.0 and group 2 ( 7.1-8.0 HbA1c). The no of antivegf injections increased in all 3 groups but statistically not significant. Significant inverse correlation of baseline HbA1c with vision at 12 month ( r = - 0.40, p<0.01) and positive correlation with central macular thickness. (r=0.53 p<0.01). Conclusion: Initial baseline Hba1c is strongly related with visual and anatomic outcome at 12 months . Number of injections were increased according to HbA1c in all 3 groups but statistically not significant may be due to the use of economical bevacizumab injection. Keywords: diabetic macular edema; bevacizumab; hemoglobin A1c; intravitreal injection;